ANALISIS PELAKSANAAN LAYANAN SAPA PUSTAKAWAN ONLINE DI PERPUSTAKAAN IAIN KUDUS - Radiya Wira Buwana (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The Sapa Pustakawan Online Service is an online-based information search service at the IAIN Kudus Library. The service utilizes Telegram's social media as a service medium for users. This study aims to analyze how the application of the Sapa Pustakawan Online service at the IAIN Kudus Library. This research was conducted using a qualitative research approach with a descriptive type of research. The data collection methods used in this study include observation, interview methods, and literature study methods. The observation method is used to make observations on service activities by librarians to users in the telegram group Sapa Pustakawan Online at IAIN Kudus Library. Then, the interview method was used to extract research data from the Head of the IAIN Kudus Library and the librarian at the IAIN Kudus Library regarding the application of the Sapa Pustakawan Online service. The method of collecting data through literature study is extracting data by using literature sources that are in accordance with the research theme. From the research, it can be concluded that the Sapa Pustakawan Online service is able to provide easy information search services, fast information search services, and capable information search services.